Case Report: Long Term Follow Up of Bladder Exstrophy Repaired in Stages with Complete Urinary Continence - Galya G. Alsharif,; Mazen O. Kurdi,; Nizar J. Kamal,; Jamal S. Kamal, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Bladder exstrophy is a rare congenital anomaly displaying symptoms such as the urinary bladder turned inside out, an exposed dorsal urethra, foreshortened penis, anteriorly displaced anus and widely separated symphysis pubis. This abnormality is managed by many methods, one of which includes a functional reconstruction. The major goals of surgical intervention are: Preservation of the renal function, achieving urinary continence with adequate sexual function and acceptable cosmetic appearance. In this report we present a long term follow up (25 years) of a male patient with classical type bladder exstrophy, managed at our hospital in stages, he is fully continent and voids spontaneously without clean intermittent self-catheterization, with normal renal function, adequate penile erection and has ejaculation.